Contextual and dispositional antecedents of organizational citizenship behavior: does occupation make a difference? - İmer, Havva Pınar. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
The present study aims to explain organizational citizenship behavior (OCB), specifically helping, civic virtue and sportsmanship behaviors within a framework of their antecedents. OCB is investigated in relation to its contextual antecedents of organizational and occupational commitments and perceptions of organizational and occupational support, together with dispositional affect and work values. The study also attempts to extend the literature with its focus on two occupations, engineering and teaching, to investigate if respondents representing two highly professional and distinct occupations display any differences in explaining OCB in relation to its antecedents. The questionnaire was developed based on a literature review and administered to 180 teachers and 180 engineers working in private sector in Istanbul. Perceptions of occupation related support from the organization (OPOS) were measured by modifying four of the perceived organizational support items, the validation of which is detailed. Factor analyses suggested a five factor structure for work values named as involvement, prestige, accomplishment, social and material values and a two factor structure for negative affect (NA), internal NA (NA-I) and NA resulting from relations with others (NA-O). As a result of the regression analyses, helping behavior is significantly explained with normative occupational commitment, perceptions of occupation related support from the organization, positive affect, involvement and social work values in a positive way, while with prestige work values in a negative way. Civic virtue behavior is predicted significantly by affective organizational commitment, perceptions of occupation related support from the organization, positive affect and involvement work values in a positive direction. Moderation analysis yielded a modest significance for the moderation of occupation between involvement work values and civic virtue behaviors. Sportsmanship behavior is explained with perceived organizational support and accomplishment work values in a positive way, while with NA-I and NA-O in a negative way. The results of the t-tests comparing the two occupational groups reveal differences between teachers and engineers for each variable but continuance occupational commitment, material work values and NA-O. The findings of the study point to the importance of both context and dispositions in explaining OCBs. Occupation related support perceptions and work values, together with other contextual and dispositional antecedents, come out as powerful candidates in explaining organizational citizenship behaviors.
Keywords: Organizational behavior.; Organizational effectiveness.